Pelatihan dan Pendampingan Pembuatan Briket Batok Kelapa yang Ramah Lingkungan dalam Rangka Pengembangan Ekonomi Kreatif di Kelurahan Samaenre - akbar, nurhidayah; Nurwahidah, Nurwahidah; Sani, Chaerul; Irawan, Heri; Rahman, Abdul; Saifuddin Amin (PANRITA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to develop the creative economy in Samaenre Village through the use of organic waste in the form of coconut shells. The problem found was the large amount of coconut shell waste and the lack of knowledge and skills of the community in utilizing the waste into goods of high economic value. The choice of this topic is based on the importance of supporting economic growth through utilizing local resource potential. The results of this activity show that providing training and assistance in making coconut shell briquettes is able to increase public awareness about the potential of local resources, create new business ideas or business opportunities in that place, and can preserve the environment. In conclusion, this community service highlights the importance of exploring your potential and taking advantage of existing opportunities. By strengthening the understanding of awareness regarding utilization concerns in the surrounding environment, we will be able to advance the wheels of the local economy.